Electrochemical Sensors Based on Molybdenum Disulfide Nanomaterials. Issue 9 (16th July 2015) - Wang, Tanyuan; Du, Kuangzhou; Liu, Wanglian; Zhang, Jinxuan; Li, Meixian
Abstract Nanostructured molybdenum disulfide (MoS2) has been arousing great research interest in many fields in recent years due to their peculiar properties. In this short review, we introduce recent advances in nanostructured MoS2 as potential materials for construction of electrochemical sensors. The potential application prospect of the electrochemical sensors based on MoS2 nanomaterials is proposed.